UMP research grant awards in the first half of 2009 - UMP, PNC (Penerbit UMP, 2009)
In efforts to cultivate a research culture in Universiti Malaysia Pahang, the university management board has allocated a research fund of RMS million for 2009, aimed primarily at encouraging its academic staff to start doing research work.